Caracterização de criadouros artificiais de Anopheles spp. (Diptera: Culicidae) na área metropolitana da cidade de Manaus, Amazonas, Brasil - Arcos, Adriano Nobre (2012)
Mosquitoes of genus Anopheles are of great relevance in malaria epidemiology and transmission. Anophelines are holometabolous, with four developing stages: egg, larva pupa, and winged adult. The larval stage gets developed in clear water, where remains of organic matter from the neighboring vegetation, submerged vegetation and shadowed areas, can be found. Human presence in Amazonia also shows an influence in the appearance of new breeding sites: Brick factory pits, fish breeding ponds and dams, among others. The present work aims to characterize man-made breeding sites by utilizing limnolological, physiological, phycological, and entomological and bio- ecological parameters within the Manaus city metropolitan area. Ten (10) collections were carried out in man-made breeding sites in 2011 and the collected materials (larvae, water, Phytoplankton and macrophytes) samples, were forwarded to the dengue and malaria, environmental chemistry, plankton and Max-Planck laboratories at INPA for storage, identification and analyses. Canonical correlation and multiple regression statistical tests (CCA) were done so as to verify relations between biotic and abiotic parameters with the anophelines. Breeding sites presenting natural characteristics and sited close to households presented higher larval density, with a large abundance of A. triannulatus and A. darlingi. Macrophytes provide a micro-habitat for larvae and other macro invertebrates, where alga and organic matter are used for feeding. A good part of the physical chemical parameters was in accordance to CONAMA resolution; however pH and dissolved oxygen were not normal at some points, but nothing that would interfere with the environment as a whole. Canonical analysis showed relation of limno logical phosphate and conductivity parameters com the presence of A. peryassui, A. nuneztovari, A. oswaldoi and the nitrate, pH and dissolved oxygen variables showed relation with A. nimbus. Species of A. albitarsis and A. deaneorum got higher influence from turbidity, total suspended solids and temperature. We saw no relation between macrophyte, alga diversity and anopheles larval abundance, yet field observations showed breeding sites harboring a high density of microphytes and algae, to present high larval density, mainly associated to macrophytes surrounding the breeding sites. We point out the importance of monitoring these man-made breeding sites, since they contribute for maintaining malaria prone habitats all year round, along with the high possibility of malaria outbreaks in the urban area neighboring Manaus. Keywords : limnology, anophelines, larval habitat